Sintesis dan Karakterisasi Fasa Crystoballite Berbasis Silika Sekam Padi dengan Metode Sintering (Solid State) - Pulung Karo-Karo; Simon Sembiring (JIEMS (Journal of Industrial Engineering and Management Systems), 2017)
This study was carried out to characterize the formation of crystoballite crystall of silica extracted from rice husk by sintering. Extraction of silica using 5% KOH and 10% HCl solution was sintered at 750, 900, 1000,and 1100 C. The products were characterised in term of functional groups, microstructure and structure (FTIR, SEM and XRD). Characterisation of the silica using FTIR shows the presence of silanol and siloxane. XRD results confirmed that silica amorph was formed at 750C, through the intermediate formation of crystoballite 900, 1000, and 1100C. The formation of crystoballite structure increases with increasing temperature of sintering, which confirms the presence of regular particle size using SEM analysis.Keywords: Rice Husk, Silica, Crystoballite, FTIR, SEM and XRD